Fitase e grãos secos destilados com solúveis para suínos em crescimento - Silva, Daniela Rocha da (2017)
The objective of this study was to evaluate the digestibility, performance and economical feasibility of inclusion of dry distillery grains (DDGS) and phytase in the diet of growing pigs. Two experiments were carried out. Experiment 1: digestibility assay to determine the effect of phytase on the nutritional values of DDGS obtained from corn ethanol production. Eight genetically homogeneous castrated male pigs with 29.35 ± 5.74 kg were housed individually in metabolism cages to perform total collection of feces and urine. Experiment 2: performance of growing pigs fed diets containing DDGS and phytase. 40 castrated male pigs from industrial crosses, of the same origin and with an initial mean weight of 47.65 ± 3.99 kg were used. The performance of the animals was evaluated by means of daily ration consumption (ADFi), daily weight gain (ADG), feed conversion (G:F) and weight gain (BW) of each experimental unit. The treatments were composed by reference diet (RD) based on corn and soybean meal, RD with 200 g kg-1 of DDGS (DDGS), RD with addition of 1,000 units of phytase (FIT) and RD with 200 g kg- 1 of DDGS and 1,000 units of phytase (D + F). From the results of study 2 an economic feasibility analysis of the use of DDGS and phytase enzyme was performed using the cost per kilogram of weight gain (PWG), economic efficiency index (EEI) and cost index (CI). The inclusion of 200 g kg-1 DDGS in diets for growing pigs increased the excretion of dry matter (DM), nitrogen (N), excreted energy (E exc.), Reducing the dry matter digestibility coefficient (DMDC), Coefficient of energy digestibility (EDC) and the metabolizable energy coefficient (MEC). The values for DM and N consumed, balance of N (NB), N digestible (DN), N metabolizable (MN), energy consumed (E cons.), digestible energy (DE) and metabolizable energy (ME) with the supply of DDGS. The animals that consumed the DDGS diets presented lower ADFi and ADG for periods 1 and total, when compared to the animals receiving the control diet. Consequently, these animals had a lower weight at the end of the experiment. The use of phytase in growing pigs in diets with no DDGS did not affect the digestibility coefficients and performance. Diets with the inclusion of 200 g kg-1 of DDGS and 1,000 units of phytase did not differ for the PWG, EEI and CI variables throughout the study period compared to the control diet. It is concluded that even with a small reduction in the parameters evaluated using DDGS, this co-product is still a viable alternative for the production of growing pigs.